Harmonization of Good Faith Acquisition – The Reason, and the Method - Radonjić, Aleksa (Pravni zapisi, 2017)
The purpose of this paper is to show that the diversity of rules on good faith acquisition among EU Member States may cause legal uncertainty and different treatment of similar cases on internal market. I try to demonstrate this diversity and the said consequences by comparing the French, the German and the Dutch approach to good faith acquisition. Based on this comparison I make a plea for harmonization of the rules on good faith acquisition for cross-border transactions only, which should include rules on transfer of ownership and which should be done via regulation. Key words: good faith acquisition, harmonization, transfer of ownership, transfer of movables.